The Influence of Transformational Leadership and Moral Integrity on Employee Performance - Yulhaidir, Aji; Lubis, Zulkarnain; Patisina, Patisina (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Employee Performance Becomes Very Important Because the Decline in Performance of Both Individuals and Groups in an Agency Can Have a Significant Impact on a Government Agency, Namely It Will Have an Impact on the Achievement of Organizational Goals. This Research Was Conducted on Civil Servant Employees at the North Sumatra Customs Office with the Aim of Determining Transformational Leadership and Moral Integrity on Employee Performance. This Research is a Quantitative Research with a Total Sampling Technique of 142 Respondents. Data Collection Techniques Using the Transformational Leadership, Moral Integrity and Employee Performance Research Scale. The Analysis Method Used in This Research is Quantitative Descriptive The Analysis Test Tool Used is SPSS Version 25.0 with the Multiple Linear Regression Analysis Method. Based on the Results of This Study, It Shows That Transformational Leadership (X1) Has a Positive and Significant Effect Partially on Employee Performance (Y). Moral Integrity (X2) Has a Positive and Significant Effect on Employee Performance (Y). The Value of Determination Coefficient (R-Square) Obtained from the Influence of Transformational Leadership and Moral Integrity on Employee Performance is 0.674. This Shows That Transformational Leadership and Moral Integrity Provide an Effective Contribution of 67.4% in Improving Employee Performance. Transformational Leadership and Moral Integrity Have a Positive and Significant Influence Simultaneously on Employee Performance.